Menganalisis Peran Advokat dalam Implementasi Keadalian Restoratif pada Kasus Kekerasan dalam Rumah Tangga untuk Pemulihan Korban - Rico Yonanda Situmeang; July Esther (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2026)
Handling cases of domestic violence (KDRT) requires an approach that not only focuses on sanctions for perpetrators, but also on the comprehensive recovery of victims. One of the appropriate methods is restorative justice, which is focused on restoring social relations, psychological recovery for the victim, and the participation of all parties involved in the process of resolving the case. In this context, lawyers play a strategic role, not only as defenders of the law, but also as facilitators of a just and supportive restorative process for victims. This study aims to analyze in depth the role of lawyers in the implementation of restorative justice in domestic violence cases, as well as identify the challenges and opportunities faced in practice. The applied approach includes normative juridical and sociological with qualitative data analysis. The findings indicate that lawyers play a crucial role in ensuring victims ' rights are protected, providing trauma-sensitive legal assistance, and encouraging restorative agreements that do not harm victims. Therefore, it is necessary to increase the capacity of lawyers, the development of more comprehensive regulations, and cooperation between sectors to support the implementation of restorative justice that is efficient and in favor of victims of domestic violence.